Handbuk ng sikolohiyang Pilipino : Handbook of Filipino psychology - Pe-Pua, Rogelia (Diliman, Quezon City : University of the Philippines Press, 2024)
Filipino psychology is the psychology born out of the experience, thought, and orientation of Filipinos. It is base on Filipino culture, language, perspective, society, and history. It is systematic and scientific in gathering information through the use of indigenous methods that are appropriate to the Filipino experience. It has wide application in different aspects of Philippine life. Filipino psychology is a good example of an indigenous psychologies with a long history and significant achievements. This collection of articles aims to be an important reference material to further develop the scholarship and teaching in psychology.
Keywords: Psychology -- Research; Social psychology -- Philippines; National characteristics, Filipino; Filipinos -- Psychology